3D-TCAD benchmark of two-gate dual-doped Reconfigurable FETs on FDSOI28 technology. (February 2023) - Navarro, C.; Donetti, L.; Padilla, J.L.; Medina-Bailon, C.; Galdon, J.C.; Marquez, C.; Sampedro, C.; Gamiz, F.
Abstract: Through 3D-TCAD simulations this work aims to demonstrate the benefits of Reconfigurable FETs based on dual doping with respect to the Schottky junctions counterparts using the 28 nm FDSOI platform. These devices feature both N and P dopant species at source and drain to allow for electron and hole symmetrical currents instead of using mid-gap metallic regions. Quasi-static results reveals much larger currents thanks to the enhanced carrier injection with analogous capacitances, leading to faster logic circuits in mixed-mode simulations. Dynamic results also show lower energy-delay products making these devices more efficient and appealing to implement reprogrammable logic. Highlights: Dual doped Reconfigurable FETs are functional with two top gates. Dual doped RFETs have greater currents than Schottky barrier RFETs. DD RFETs are more immune to manufacturing variability than SB RFETs. DD RFETs are appealing for 28 FDSOI technology to implement in-situ reprogrammable logic.